Analisis Faktor-faktor yang Mempengaruhi Financial Distress pada Perhotelan yang Dilisting di BEI Periode 2020-2024 - Daulay, Leli Anni (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the factors influencing financial distress in hotel sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. The independent variables tested in this research include room occupancy rate, operational costs, and operating income (BOPO), leverage, and liquidity. A quantitative approach was employed using multiple regression analysis, and hypothesis testing was conducted through t-tests to determine the partial effect of each variable. The results of the study indicate that the room occupancy rate has a negative and significant effect on financial distress, suggesting that higher occupancy levels can reduce the likelihood of financial hardship. In contrast, operational costs and operating income (BOPO) do not show a significant impact on financial distress, implying a neutral relationship. Interestingly, both leverage and liquidity have a positive and significant effect on financial distress, which suggests that high levels of debt and excess liquidity may actually increase the risk of financial difficulties. These findings underscore that while improving occupancy rates is crucial to financial stability, excessive borrowing and inefficient liquidity management can increase a hotel company's financial vulnerability. The implication of this study emphasizes the importance for hotel management to maintain stable occupancy rates and adopt prudent financial strategies, particularly in managing debt structure and liquidity, to mitigate the risk of financial distress and ensure long-term sustainability in a highly competitive industry.